2012
DOI: 10.1093/europace/eus188
|View full text |Cite
|
Sign up to set email alerts
|

European survey on efficacy and safety of duty-cycled radiofrequency ablation for atrial fibrillation

Abstract: AimsDuty-cycled radiofrequency ablation (RFA) has been used for atrial fibrillation (AF) for around 5 years, but large-scale data are scarce. The purpose of this survey was to report the outcome of the technique.Methods and resultsA survey was conducted among 20 centres from seven European countries including 2748 patients (2128 with paroxysmal and 620 with persistent AF). In paroxysmal AF an overall success rate of 82% [median 80%, interquartile range (IQR) 74–90%], a first procedure success rate of 72% [medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 13 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…Rates of around 1% neurologic events, including symptomatic transient ischemic attack/stroke, with duty-cycled RF ablation were recently reported in a large survey. 29 These rates are in the same range as those reported with conventional RF. 30,31 Asymptomatic cerebral infarction rates of ∼14% with irrigated-tip catheters have been reported.…”
supporting
confidence: 70%
“…Rates of around 1% neurologic events, including symptomatic transient ischemic attack/stroke, with duty-cycled RF ablation were recently reported in a large survey. 29 These rates are in the same range as those reported with conventional RF. 30,31 Asymptomatic cerebral infarction rates of ∼14% with irrigated-tip catheters have been reported.…”
supporting
confidence: 70%
“…These "single-shot" techniques were designed to create a circular ablation lesion around the PVs after the appropriate positioning of the ablation catheter at the ostium or at the antra of each PV. A number of studies have demonstrated comparable levels of success and safety profile, but shorter procedure times with these simplified methods than with the conventional point-by-point ablation [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The European survey on the efficacy and safety of PVAC® [25] included twenty centers from seven European countries, 2748 patients (77% with PAF). The mean procedure time was 122 min for paroxysmal and 145 min for persistent AF (P = 0.08).…”
Section: Technical Differences and Ablation Strategy Pvac® -Phased Rfmentioning
confidence: 99%
“…In the European survey on the efficacy and safety of PVAC® [25] (2128 patients with PAF, 620 persistent AF) 81% had a structured follow-up defined as routine Holter-ECG after a mean of 11.2 months. The survey found in PAF patients an overall success rate of 82% [median 80%, interquartile range (IQR) 74-90%], with a first procedure success rate of 72% [median 74% (IQR 59-83%)].…”
Section: Longer-term Outcomementioning
confidence: 99%